1979
DOI: 10.1097/00006842-197912000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic Correlates of Serum Indicators of Stress in Man: A Longitudinal Study

Abstract: Correlations between serum uric acid, cortisol, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol and psychometric indices of stress-namely, anxiety, hostility, and depression-were investigated in 20 students over a 2Vi month academic quarter. There were three peak periods of stress, with two occurring during midterm and final exams. The observed changes in serum cortisol were highly correlated with changes in anxiety and depression. Serum uric acid was significantly depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…4) Substantial evidence indicates that mental stress is associated with elevations in serum lipid concentration, 4) and increases in cholesterol levels following academic examinations have been documented. [5][6][7][8] The majority of the previous studies measured only cholesterol levels, while some also showed that the levels of other lipids and lipoprotein were affected. 4,8) Most of the reported studies were conducted in the Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Substantial evidence indicates that mental stress is associated with elevations in serum lipid concentration, 4) and increases in cholesterol levels following academic examinations have been documented. [5][6][7][8] The majority of the previous studies measured only cholesterol levels, while some also showed that the levels of other lipids and lipoprotein were affected. 4,8) Most of the reported studies were conducted in the Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The majority of the previous studies measured only cholesterol levels, while some also showed that the levels of other lipids and lipoprotein were affected. 4,8) Most of the reported studies were conducted in the Caucasian population. This present study was conducted in the black African population, in whom coronary heart diseases were known to be low [9][10] ; recently, however, high cholesterol levels have been reported in apparently healthy businessmen in a certain community in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The body's reaction to stress is multidimensional, and includes gastrointestinal, cardiovascular, behavioral, analgesic, immunologic, endocrinologic, psychologic-behavioral and psychopathologic changes [Anisman and Zacharko, 1982;Akiskal and McKinney, 1973, 19751,Depending on the perspective of the investigator, the phenomenon of stress has been characterized using neuroendocrine measures (such as changes in serum ACTH, cortisol, betaendorphin, growth hormone, arginine-vasopressin, and prolactin), changes in pulse and blood pressure, changes in peripheral sympathetic neurohormones, and changes in mood and behavior, including the induction of negative affects such as anxiety, depression, and hostility [Anisman et al, 1981;Selye, 1936Selye, , 1956Selye, , 1976Usdin et al, 1980;Rabkin and Streuning, 1976;Weiss, 1971a,b,c;Francis, 1979;Baum et al, 19821. Information from animal studies has accumulated suggesting that the manifestations of stress may be mediated by complex alterations in central neurotransmitters, including norepinephrine, dopamine, serotonin, and gamma amino butyric acid (GABA) [Anisman and Zacharko, 19821. Acetylcholine, a major central and peripheral autonomic neurotransmitter, may also have a role in the mediation of stress responses, although such a role for this chemical has not been widely investigated.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Nevertheless, although this kind of study has been done ever since 1914 16 and in that time has generated a considerable amount of scientific literature, there are still some methodological issues that compromise their findings. Stowell reviewed these limitations and made some recommendations for future research.…”
Section: Academic Examinations and Psychological Stressmentioning
confidence: 99%
“…Francis, in a longitudinal study, found that depression and hostility, as well as anxiety, were sensitive to university examinations. 9 In a cross-sectional design, Farne and Sebellico reported that tension, depression, vigor, fatigue and confusion were associated with academic examinations, but that anger was not. 18 Also with a cross-sectional design, McIntyre et al reported that the stress of an imminent examination was associated with an increased Negative Affect, an aspect of affect that reflects a person's general level of subjective distress, but no variation in Positive Affect, which reflects positive emotional experiences.…”
Section: Academic Examinations and Psychological Stressmentioning
confidence: 99%